2021
DOI: 10.31462/jcemi.2021.03151172
|View full text |Cite
|
Sign up to set email alerts
|

Application areas of augmented reality and virtual reality in construction project management: A scoping review

Abstract: Augmented reality (AR) and virtual reality (VR) are advanced technologies that can provide significant advantages to the construction industry. In recent years, many researchers have focused on implementing AR and VR technologies in the construction project management domain, where these technologies have shown a significant contribution to the advancement of the construction project management aspects in many areas. However, there is a lack of a structured review that synthesizes the existing body of knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 87 publications
(173 reference statements)
0
7
0
1
Order By: Relevance
“…It is also observed that while the available review studies in the literature are presented for different use cases in the AEC industry ( Figure 8 ), the authors of this paper did not identify any review or discussion study about the use of XR for condition assessment of civil engineering structures. A total of 25 literature review studies were identified that consider VR, AR, and MR separately [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], or VR and AR together [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], or VR, AR, and MR all together (which is XR) [ 61 , 62 ] in the AEC industry. Only two of these studies consider XR in their review, where they studied BIM in AEC.…”
Section: Discussionmentioning
confidence: 99%
“…It is also observed that while the available review studies in the literature are presented for different use cases in the AEC industry ( Figure 8 ), the authors of this paper did not identify any review or discussion study about the use of XR for condition assessment of civil engineering structures. A total of 25 literature review studies were identified that consider VR, AR, and MR separately [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], or VR and AR together [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], or VR, AR, and MR all together (which is XR) [ 61 , 62 ] in the AEC industry. Only two of these studies consider XR in their review, where they studied BIM in AEC.…”
Section: Discussionmentioning
confidence: 99%
“… [ 99 ] AI Application areas of augmented reality and virtual reality in construction project management: A scoping review 2021 Developing an assistive interface for a teleoperated crane by implementing path planning in the context of heavy equipment operator training. [ 53 ] ML A critical review of virtual and augmented reality (VR/AR) applications in construction safety 2018 The sequence includes safety training and education, hazards recognition and identification, and safety instruction and inspection. [ 56 ] ML Using Deep Learning Artificial Intelligence to Improve Foresight Method in the Optimization of Planning and Scheduling of Construction Processes 2022 More rapidly review and recommend more planning options for scheduling complex construction projects [ 48 ] …”
Section: Applications Of Ai and ML In Construction Project Lifecycle ...mentioning
confidence: 99%
“…Architecture and engineering design [17,21,23,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Building construction [17,[20][21][22][23][24][25]27,[29][30][31][47][48][49][50][51][52][53][54][55][56] Building operation and management [17,18,21,23,26,28,54, Selected articles concerning XR application in building operation and management were further divided into VR and AR/MR categories, each articulated in different domains according to their possible use in building facility management as shown in Table…”
Section: Xr Application Field Selected Articlesmentioning
confidence: 99%
“…Delgado et al [24] presented a systematic study of the factors that limit and drive the adoption of AR and VR in a construction sector-specific context. Albahbah, et al [25] reviewed seven applications of AR that may benefit the construction industry, namely, safety management, communication and data acquisition, visualization, construction management education, progress tracking, quality management, and facility management. Zhu et al [26] presented a state-of-the-art review of the application of virtual and augmented reality technologies for emergency management in built environments, while Li et al [27] reviewed VR and AR applications in construction safety.…”
Section: Introductionmentioning
confidence: 99%